Burden and Management of Urolithiasis in a Newly Established Urology Unit of a Tertiary Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Urolithiasis is the third most common affliction of the urinary tract that constitutes a significant burden on the practice of urology. The incidence and prevalence of urolithiasis are increasing globally.Objective:To assess the burden, presentation, and management of urolithiasis in our hospital.Materials and Methods:It was a retrospective descriptive study of patients who were managed for urolithiasis at the urology unit of our hospital between January 2015 and December 2019. Ethical approval was obtained. Patients’ bio-data, clinical features, treatment, and complications were extracted from their medical records and entered into the proforma. The generated data were analyzed using SPSS version 21.0.Results:Complete medical records of 68 patients were retrieved. This constituted about 40.6% of urologic patients managed within the period. Their age ranged from 9 to 86 years with the mean age of 43.2 years ± 8.8 standard deviation (SD). The M F was 1.8:1. Students were predominant (29.4%). Others were traders, housewives, civil servants, and farmers. The majority of the patients presented with flank pain (64.7%) and mostly had renal pelvis stone (35.3%). Others had bladder stone (16.2%) and stag horn calculus (11.8%). Nearly all our patients were treated by open surgeries (98.5%) and most (72.1%) did not have any postoperative complication.Conclusion:Urolithiasis constitutes significant workload for urologists in our environment predominantly affecting young and middle-age males. The stones were predominantly in the upper urinary tract with a significant number of stag horn calculi. Despite the non-availability of uroendoscopic facilities, the majority of our patients had good outcome.